ChemInform Abstract: Pretreatment and Conversion of Lignocellulose Biomass into Valuable Chemicals. Issue 27 (16th June 2016) - Putro, Jindrayani Nyoo; Soetaredjo, Felycia Edi; Lin, Shi‐Yow; Ju, Yi‐Hsu; Ismadji, Suryadi
Abstract: Review: 252 refs.